Avatara Dalam Mahabharata - Ananda, I Nyoman (Jurnal Penelitian Agama Hindu, 2023)
Hinduism teaches about avatara, namely the descent of the divine to the worldly realm and mingling with human life. This teaching is considered to have originated from the Purusha Sukta of the Rg Veda and then developed in the Itihasa and Puranas. This study focuses on the Mahabharata text that influences the religious life of Hindus in Indonesia, especially in Bali. The entry of transnational teachings known as sampradaya caused unrest and conflict in Hindu society, especially in Bali. One of the debates is the worship of Krsna as God which is considered to deviate from Hindu teachings in general which regard Krsna as an avatar of Visnu. This study aims to analyze the concept of avatara contained in the Mahabharata text, its origin, character, and role in upholding dharma (truth). The theory used is the theory of Semiotics, and the theory of Hermeneutics. Types and research data using qualitative data. Primary data sources are Mahabharata manuscripts and secondary data sources include research results, books, and internet sources. The research instrument uses a dictionary as a translation medium. At the stage of presenting data analysis using formal and informal methods, it was found that the avatara concept originated from Purusa Sukta which was sourced from the Rg Veda and then developed in the Mahabharata. Mahabharata describes avataras that appear every age and avataras with special missions. Krsna is described as having two characters as a divine being free from the influence of the world with all its rules and as an ordinary human being bound by this world.